When the cognitive subject is an active woman: The case of feminist studies - Worek, Barbara (Journal of Public Governance, 2018)
The debates conducted by the Kraków Circle revolve around three notions: the cognitive subject, cognition, and action. The discussion in question focussed on the determinants of cognition, the relationships between cognition and action as well as the possible limitations imposed on the cognitive subject. It makes sense, however, to inquire about the impact of gender of the cognitive subject on her cognition and action. Is gender only one of many differences between cognitive subjects? Or else, is it a crucial distinction that defines both the nature of the cognitive process and the relationships between the mode of description of the world and the imperatives that should be followed in action? In an attempt to answer these questions, the authors focus on feminist research, which is committed, i.e. it crosses the line between cognition and action. In extreme cases, cognition becomes subordinated to action, since the overriding goal of cognition is to effect intentional social change.